A cytotoxic tantalum(v) half-sandwich complex: a new challenge for metal-based anticancer agents - Štarha, Pavel; Trávníček, Zdeněk; Dvořák, Zdeněk (Chemical communications (Cambridge, England), 2018)
Despite the biological relevance of complexes of various transition metals, tantalum complexes have long been neglected by bioinorganic chemists. Herein, we demonstrate potential chemotherapeutic applicability of the [Ta(η5-Cp*)Cl2(salaph)] (1) complex, containing deprotonated Schiff base 2-{(E)-[(2-hydroxyphenyl)imino]methyl}phenol (H2salaph), which shows strong cytotoxicity in cancer cells, related to the induction of apoptosis and apoptosis-related processes, but shows low cytotoxicity in healthy cells.
Keywords: Cytochromes c; Ligands; reaktivní formy kyslíku; Humans; ligandy; Schiffovy báze; tantal; komplexní sloučeniny; reaktivní formy dusíku; Schiff Bases; cytochromy c; Antineoplastic Agents; rozpustnost; Membrane Potential, Mitochondrial; lidé; Reactive Nitrogen Species; Coordination Complexes; oxaliplatin; molekulární struktura; Reactive Oxygen Species; apoptóza; Molecular Structure; Solubility; nádorové buněčné linie; protinádorové látky; organoplatinové sloučeniny; Hepatocytes; Cell Line, Tumor; membránový potenciál mitochondrií; Tantalum; hepatocyty; Organoplatinum Compounds; Apoptosis; Oxaliplatin